Hak Mewaris Bagi Suami yang Tidak Pernah Menafkahi Istri dan Keluarga Dalam Perspektif Hukum Islam - Istri Dianita, Gusti Agung Sagung; Novy Purwanto, I Wayan (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 7 No 02 (2022), 2022)
The purpose of this paper was to analyze and identify marital status if the husband leaves his wife without clarity. In addition, this paper also examines the right to inherit for a husband who has left his wife without clear reasons and without ever fulfilling obligations such as providing a living for his wife during marriage based on the prevailing laws and regulations in Indonesia, especially in the perspective of Islamic law. This paper used a normative legal research method using a statutory approach, a concept approach and an analytical approach. The results of the study indicated that the status of a marriage does not break up automatically only because the husband leaves his wife for 2 (two) consecutive years without the permission of the other party and without a valid reason or for other reasons beyond his ability and in the case that the marriage has not been terminated, a man -Men and women are still considered as legal husband and wife, even though there is negligence of the husband in carrying out his obligations, it still provides legitimacy for the man in his position as a widower of the heir hence, he is entitled to the right to inherit.